Diasporic Masculinities: 'Reflections on gendered, raced and classed displacements' - Fataneh Farahani (Nordic Journal of Migration Research, 2012)
This article is based on reflections that have grown during the ongoing research on construction of masculinities and sexualities in different diasporic spaces. By focusing on theoretical and contextual reflections regarding conditions of leaving, arrival and residency among Iranian-born men who live in Sydney, Stockholm and London, this article focuses on intersecting factors that construct masculinities in different diasporic spaces. Migratory masculine subjectivities are not only shifting and plural, but also reveal the multiple interactions of factors such as race, age, class, self and community, past and present, the political and the religious and through the continual negotiation of identity.